Evaluation of Temperature Regulation Efficiency of a Bilayer Coating on Glass with Evaporative and Radiative Cooling for Energy Management - Huanying Zhang; Yonghang Yu; Dedong Ji; Chen Zhou; Shengyang Yang (Molecules)
With the increasing demand for energy-efficient and sustainable building materials, innovative cooling technologies have become a key focus in the construction industry. This study developed a double-layer cooling coating integrating evaporation and radiation mechanisms. The first layer consists of a TiO2/PUA radiation layer, where rutile TiO2 is incorporated into polyurethane acrylate (PUA) resin to enhance solar reflectivity. The second layer is a P(NVP-co-NMA) hydrogel, which evaporates water at high temperatures and absorbs moisture from the air at low temperatures, eliminating the need for additional water supply systems. The TiO2/PUA@P(NVP-co-NMA) coating demonstrates high solar reflectivity and infrared emissivity, effectively reducing indoor temperatures by dissipating heat through water evaporation and radiative cooling. Testing showed a temperature reduction of approximately 7.6 °C in a small house with this coating under simulated conditions. This material demonstrates favorable properties that may make it suitable for applications on building roofs and exterior walls, potentially addressing some limitations of conventional evaporative or radiative cooling systems. Its observed multi-effect cooling performance indicates promise for contributing to energy savings in sustainable building designs.